Randomized symmetric McEliece cryptosystem based on generalized Reed-Solomon codes - Шевчук, О.С. (Radiotekhnika, 2020)
One of the actual problems of modern cryptography is the design of practical post-quantum cryptosystems whose security is based on the complexity of solving one computationally challenging problem, in the same way as the security of the RSA cryptosystem is based on the complexity of integer factorization. A promising class of such cryptosystems is formed by code-based cryptosystems the first asymmetric of which is the McEliece cryptosystem. The purpose of this work is to design and research a symmetric version of the McEliece cryptosystem based on generalized Reed-Solomon codes. These codes were chosen because they exist for all natural values of the parameters (the length and dimension of the code) and they are maximal distance separable allowing a wide range to change the characteristics of the relevant cryptosystems. In addition, very fast decoding algorithms are known for these codes. Asymmetric cryptosystems based on the generalized Reed-Solomon codes are not secure because for them there are efficient algorithms for recovering private keys from public keys. A symmetric code cryptosystem is proposed that is more efficient (in terms of the length of the secret key for given security requirements) compared to the LPN-C cryptosystem. An estimate of the security of the proposed cryptosystem relative to an attack with the chosen plaintext is obtained and an algorithm for selecting parameters for constructing this cryptosystem is proposed. The proposed cryptosystem is compared with the LPN-C cryptosystem along the key length for a given lower limit of security to the attack in question.